Spectrally-efficient 17.6-Tb/s DWDM optical transmission system over 678 km with pre-filtering analysis - L. H. H. Carvalho; E. P. Silva; R. Silva; J. P. K Perin; J. C. R. F. Oliveira; M. L. Silva; P. P. G. Cardoso; A. Paradisi (Journal of Microwaves, Optoelectronics and Electromagnetic Applications)
We present and analyze a 17.6-Tb/s DWDM optical transmission composed of 79 channels with 224-Gb/s RZ-DP-16QAM modulation format per-channel and coherent detection. A maximum reach of 678 km is obtained with an optical recirculation loop composed by 226 km of pure-silica core fibers and EDFA amplification only in a 50-GHz grid system with spectral efficiency of 4.2-b/s/Hz. Also, a 25-GHz Gaussian optical pre-filter is applied to each channel and the same reach of 678 km is obtained in a 37.5-GHz channel grid system with spectral efficiency of 5.6-b/s/Hz. These results demonstrate a 33% system capacity improvement without transmission penalties.